Task Force on Principles and Metrics for Innovation in Sustainable Agri-food Systems: Final Report - Zurek, M.; Hebinck, A.; Wirths, J.; Al-Malalha, M.; Crawford, S. (Commission on Sustainable Agriculture Intensification, 2022)
A huge increase in investment for innovation in sustainable agri-food systems (SAS) will be critical for meeting the objectives of the UN Sustainable Development Goals and the Paris Climate Agreement. Currently only a small fraction of investment addresses environmental or social goals together with productivity increase. A major challenge for both innovators and innovation investors is determining whether an investment ‘counts’ as one likely to promote both environmental and/or social sustainability. A way forward is to establish a clear set of principles for determining which innovations and innovation processes count as promoting SAS, together with guidance for how to operationalize these principles. Currently though there is a gap in the intersecting area of principles for innovation in SAS, with various principles existing for sustainable agriculture (in general), and others for innovation and innovation systems. For this reason, the Commission on Sustainable Agriculture Intensification (CoSAI) set out to create principles that cover both the outcomes and processes of innovation in SAS. This report presents the Principles for Innovation in Sustainable Agri-Food Systems as developed by a multi-stakeholder group of research agencies, investors, private sector and NGO representatives, and watchdog organizations. It describes the process including task force composition, public consultation, pre-piloting and next steps. The report furthermore provides background for the selection of principles and describes the operationalization framework for the pilot version of the Principles as developed until December 2021